SERVICE QUALITY ANALYSIS OF MOBILE-BASED FANDOM COMMUNITY APPLICATION USING E-SERVQUAL AND IPA - Itsna Siha Arzaqi Adma Nasruddin; Rio Guntur Utomo; Rahmat Yasirandi (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Using a modified e-service quality framework and the Importance Performance Analysis (IPA) approach, this study assesses the quality of service quality of Weverse and LYSN mobile apps. Information was gathered from 132 individuals who use these platforms regularly and are 22 years old. The findings indicate that Weverse and LYSN must improve to meet customer expectations, especially in response time, app stability, and refund policies. However, data security and ease of use effectively satisfy users' expectations. To increase overall user happiness, developers should prioritize improving underperforming areas while maintaining high standards in high-performing areas.